Child Development at the Intersection of Emotion and Cognition. 2010
DOI: 10.1037/12059-006
|View full text |Cite
|
Sign up to set email alerts
|

Hot executive function: Emotion and the development of cognitive control.

Abstract: Young children's ability to act deliberately in light of their knowledge is obviously limited. During the 1st few years of life, however, children change from relatively helpless creatures who must rely on their caregivers to fulfill even their most basic needs into complex intellectual and emotional beings who are able to consider alternative perspectives on a situation, plan ahead, and act in a conscious, goal-directed fashion. These changes in children's behavior are studied under the rubric of executive fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
92
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 58 publications
5
92
0
3
Order By: Relevance
“…This pattern is consistent with the idea of an age-related decrease in susceptibility to interference from salient rewardrelated information, and it suggests that decisionmaking develops in a similar fashion across several cultural contexts (Zelazo et al, 2009;Zelazo et al, 2005).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This pattern is consistent with the idea of an age-related decrease in susceptibility to interference from salient rewardrelated information, and it suggests that decisionmaking develops in a similar fashion across several cultural contexts (Zelazo et al, 2009;Zelazo et al, 2005).…”
Section: Discussionsupporting
confidence: 74%
“…In the delay of gratification choice paradigm, children are asked to choose between a smaller immediate reward and a larger delayed reward. Compared to 4-year-olds, 3-year-olds more often choose the smaller immediate reward instead of the larger delayed reward (e.g., Hongwanishkul et al, 2005), demonstrating their difficulties in inhibiting their desires (Zelazo et al, 2009;Zelazo et al, 2005). Although some studies have suggested that emphasis on delay of gratification was similar across different cultures (e.g., Godoy & Jacobson, 1999), other studies on delay of gratification tasks have shown that culture, social norms, and social learning (Gallimore, Weiss, & Finney, 1974) may influence children's decision making.…”
mentioning
confidence: 99%
“…Hot executive functions refer to cognitive functions that are recruited in situations that are emotionally or motivationally significant because they involve reward/punishment. These executive functions are subserved by the ventromedial prefrontal cortex and its associated pathways (Zelazo & Muller, 2002;Zelazo, Qu, & Kesek, 2010). On the other hand, cool executive functions are purely cognitive in nature, such as working memory, planning, set-shifting and attentional processes, and rely on the lateral prefrontal cortex (Zelazo & Carlson, 2012;Zelazo & Cunningham, 2007;Zelazo & Muller, 2002;Zelazo et al, 2010).…”
Section: Executive Functioningmentioning
confidence: 99%
“…This has led some researchers to suggest that psychopathy may be marked by specific executive dysfunction, namely dysfunction on measures of hot executive function and intact performance on measures of cool executive function (Lapierre et al, 1995;Snowden et al, 2013). Hot executive functions refer to cognitive functions that are recruited in situations that are emotionally or motivationally significant because they involve reward/punishment, and are believed to be subserved by the orbital-ventromedial prefrontal cortex and its associated pathways (Zelazo & Muller, 2002;Zelazo et al, 2010). In contrast, cool executive functions are purely cognitive in nature, such as working memory, planning, set-shifting and attentional processes, and are believed to rely on the lateral prefrontal cortex (Zelazo & Carlson, 2012;Zelazo & Cunningham, 2007;Zelazo & Muller, 2002;Zelazo et al, 2010).…”
Section: Hot and Cool Executive Functionmentioning
confidence: 99%
See 1 more Smart Citation